HIV/AIDS-associated beliefs and practices relating to diet and work in southeastern Uganda - Komwa, Maction K; Jacobsen, Kathryn H; Parker, Dawn C (Journal of Health, Population and Nutrition, 2010)
To explore beliefs relating to diet, work, and HIV/AIDS among the Busoga of rural southeastern Uganda, a cross-sectional survey of 322 adults was conducted in 2007 in Mayuge district, Uganda. Of these adults, 56 were HIV-infected, 120 had a family member with HIV/AIDS, and 146 were in households without HIV-infected members. More than 74.2% of the adults knew someone with HIV/AIDS, and more than 90% correctly identified transmission modes and prevention methods of HIV. In total, 93.2% believed that a person with HIV should work fewer hours to conserve energy but all the three participant groups reported the same working hours. Also, 91.6% believed that a person with HIV infection should eat special nutritious foods, and the participants with HIV infection reported eating more fruits (p=0.020) and vegetables (p=0.012) than other participants. The participants expressed a consistent set of health beliefs about practices relating to HIV/AIDS. Key words: Acquired immunodeficiency syndrome; Beliefs; Cross-sectional studies; Diet; HIV; Knowledge, attitudes, and practice; Nutrition; Uganda DOI: 10.3329/jhpn.v28i1.4526 J Health Popul Nutr 2010 Feb; 28(1): 76-85